Potential Feedstock Sources for Ethanol Production in Florida - Mohammad Rahmani; Alan Hodges (EDIS)
FE650, a 9-page fact sheet by Mohammad Rahmani and Alan Hodges, presents information on the potential feedstock sources that may be used for ethanol production in Florida. Sugarcane, corn, citrus byproducts, and sweet sorghum are discussed. Includes references and tables. Published by the UF Department of Food and Resource Economics, July 2006.